Geographical Variations in Host Predisposition to COVID-19 Related Anosmia, Ageusia, and Neurological Syndromes - Kumar, A Aravin; Lee, Sean Wei Yee; Lock, Christine; Keong, Nicole CH (Frontiers in Medicine, 2021)
The novel coronavirus disease (COVID-19), has become the most critical global health challenge in recent history. With SARS-CoV-2 infection, there was an unexpectedly high and specific prevalence of olfactory and taste disorders (OTDs). These high rates of hyposmia and hypogeusia, initially reported as up to 89% in European case series, led to the global inclusion of loss of taste and/or smell as a distinctive feature of COVID-19. However, there is emerging evidence that there are striking differences in the rates of OTDs in East Asian countries where the disease first emerged, as compared to Western countries (15.8% vs. 60.9%, p-value < 0.01). This may be driven by either variations in SARS-CoV-2 subtypes presenting to different global populations or genotypic differences in hosts which alter the predisposition of these different populations to the neuroinvasiveness of SARS-CoV-2. We also found that rates of OTDs were significantly higher in objective testing for OTDs as compared to subjective testing (73.6% vs. 60.8%, p-value = 0.03), which is the methodology employed by most studies. Concurrently, it has also become evident that racial minorities across geographically disparate world populations suffer from disproportionately higher rates of COVID-19 infection and mortality. In this mini review, we aim to delineate and explore the varying rates of olfactory and taste disorders amongst COVID-19 patients, by focusing on their underlying geographical, testing, ethnic and socioeconomic differences. We examine the current literature for evidence of differences in the olfactory and gustatory manifestations of COVID-19 and discuss current pathophysiological hypotheses for such differences.